The Enforcement of Anti-Corruption Laws in Indonesia and Sierra Leone: A Socio-Legal Perspective - Thomas Sheku Marah (Rechtenstudent, 2024)
Corruption stands as a major threat that affects governance systems, economic progress, and justice in both Indonesia and Sierra Leone. The anti-corruption legal frameworks, which include Law No. 31 of 1999 and the Sierra Leone Anti-Corruption Act of 2008 (amended in 2019), face major socio-legal Challenges during enforcement. The article utilizes a socio-legal methodology for comparing anti-corruption enforcement performance between Indonesia and Sierra Leone. The paper examines institutional mechanisms through the Indonesian Corruption Eradication Commission (KPK), together with the Sierra Leone Anti-Corruption Commission (ACC), to evaluate their achievements and constraints within their respective political and cultural environments. The research shows that political interference, weak institutions, and low public confidence exist in both countries, whereas enforcement bodies maintain different levels of independence and authority. The research establishes that institutional independence requires strengthening, public participation needs enhancement, and international cooperation should be promoted through a comparison of these two jurisdictions. The article advances knowledge about anti-corruption law enforcement dynamics while providing valuable policy insights for developing democracies which face corruption challenges including Indonesia and Sierra Leone.